Community banks, money and labour productivity. (20th August 2019) - Smoluk, Bert J.
Abstract: Does money affect productivity? We examine whether bank deposits, a measure of the money supply that excludes currency in circulation, influence labour productivity. Banks deposits are special in that they facilitate transactions and, in aggregate, add liquidity and credit availability to a region. By exploiting the distribution of community bank deposits across the states, we test the hypothesis that money is an input to the production function under a variety of panel data methods. We find evidence that bank transaction deposits and total deposits along with other production function inputs such as wages, labour and gross state product are cointegrated across the states; however, the economic contribution of money to labour productivity appears limited.